1995
DOI: 10.1002/mc.2940130403
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency of CDKN2 mutation in endometrial carcinomas

Abstract: The CDKN2 gene on chromosome 9p21 encodes the p16 inhibitor of cyclin D/cyclin-dependent kinase 4 complexes. Mutations and deletions of CDKN2 have been frequently identified in cell lines, whereas most primary tumors have demonstrated a lower frequency of alteration. To assess the role of CDKN2 in endometrial tumorigenesis, 34 tumor samples were examined for loss of heterozygosity at 9p21 and mutation in CDKN2. To identify tumors that had lost 9p21, samples were genotyped with markers flanking the CDKN2 locus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Our findings should be considered in light of previous reports regarding p16 and/or p15 in human uterine tumours (Hatta et al, 1995;Kelly et al, 1995;Peiffer et al, 1995;Hirama et al, 1996;Wong et al, 1997;Kim et al, 1998;Munirajan et al, 1998). Hatta et al (1995) found no mutations, deletions, or rearrangements in 15 endometrial carcinomas.…”
Section: Discussionsupporting
confidence: 74%
“…Our findings should be considered in light of previous reports regarding p16 and/or p15 in human uterine tumours (Hatta et al, 1995;Kelly et al, 1995;Peiffer et al, 1995;Hirama et al, 1996;Wong et al, 1997;Kim et al, 1998;Munirajan et al, 1998). Hatta et al (1995) found no mutations, deletions, or rearrangements in 15 endometrial carcinomas.…”
Section: Discussionsupporting
confidence: 74%
“…The low frequency of p16 alterations in the present series is in line with other studies. [11][12][13][14]16 We have previously reported that loss of nuclear p16 protein expression is associated with aggressive endometrial carcinomas and poor prognosis. 15 In line with this, we now demonstrate that alterations in the p16 gene also are associated with an aggressive phenotype, even though small numbers in the present series call for caution in the conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…The median follow-up period for the survivors was 9 years (range [5][6][7][8][9][10][11][12][13][14]. None of the patients were lost due to insufficient follow-up data.…”
Section: Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the alternative exon 1␤, encoding parts of the ARF product, was not included in the analysis, our study does not support a role of CDKN2A/p16 or ARF inactivation in development of endometrial carcinomas, which is in agreement with the majority of previous studies. 36,37 However, the alternative mechanism of promoter hypermethylation or homologous deletion of the gene may be involved in these tumors. 66 Few tumors included in this study make it impossible to suggest a model for endometrial tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%